Utilization of Honey Apis dorsata as Antiosteoporosis on Requirements of Bone Calcium Ash Density on Ovariohysterectomized White Rat (Ratus norvegicus) - Ibrahim, Muhammad Huda Ramadhan; Hasib, Abdullah Hasib; Rohmah, Siti Nur; Abani, Salsabilla; Yordan, Samsi; Yudaniayanti, Ira Sari (KnE Life Sciences, 2017)
The purpose of this study was to determine the effect of honey bee Apis dorsata as anti-osteoporosis in calcium ash density (CAD) of bone in osteoporotic-induced rats. The target of this study was to know bone calcium levels after being given honey bees Apis dorsata. In this study, 35 female white rats (Ratus norvegicus) mature was used with weight 200gr. Divided into 5 groups, 2 control groups and 3 treatment groups. The negative control group (SH) was not induced by osteoporosis and was given the only aquadest of 1.5 ml/day. Whereas the positive control group was induced by osteoporosis (OH) and was given only aquadest 1.5 ml/day. T1, T2 and T3 treatment groups were given bee honey with various doses including 1g / kg ad 1.5 ml aquadest, 2g / kg BB ad 1.5 ml aquadest and 3g / kg BB ad 1.5 ml aquadest. Then after 12 weeks, white rats were sacrificed for lumbar vertebrae. Furthermore, the sixth lumbar spine os vertebrae will be examined for calcium bone ash content. The data were obtained was analyzed using statistical analysis of variance (ANOVA) for the results of the calcium ash content data Keywords: Honey; Osteoporosis; CAD